Potential use of anatomical and physiological characteristics in the selection of coffee progênies - Castanheira, Dalyse Toledo; Rezende, Tiago Teruel; Baliza, Danielle Pereira; Guedes, Janine Magalhães; Carvalho, Samuel Pereira de; Guimarães, Rubens José; Viana, Mariana Thereza Rodrigues (Coffee Science - ISSN 1984-3909, 2016)
The objective was to evaluate the potential use of morphological and physiological characteristics in the selection of coffee progenies. For the anatomical and physiological, were sampled twenty progenies coming from the three types of origins groups of experimental population installed in UFLA. The design was completely randomized with two evaluation periods. The progenies have studied genetic variability has been a divergence between them. In general, for the thickening of the leaf tissue the genetic variation of the progenies is higher in the dry season, indicated that there is greater variability among the families in that period. There is potential for the use of morphological and physiological characteristics as a tool in the selection of coffee progenies tolerant water stress.